Luneburgova leča - Razpet, Marko (Obzornik za matematiko in fiziko, 2013)
In this contribution the Luneburg lens wherein the monocromatic light rays propagate along elliptical arcs is presented. Some properties of the corresponding ellipses are derived.
Keywords: physics; svetloba; mathematics; optika; leča; elipsa; ellipse